Protein network formation during pound cake making: The role of egg white proteins and wheat flour gliadins. (December 2016) - Deleu, Lomme J.; Wilderjans, Edith; Van Haesendonck, Ingrid; Brijs, Kristof; Delcour, Jan A.
Abstract: During pound cake baking, structure sets as a result of starch gelatinization and protein network formation. These processes are crucial for pound cake quality. However, the relative contribution of the different proteins to the network formation has hardly been studied. Here, protein extraction in different media and size-exclusion HPLC analysis are used to monitor 15 N-labeled egg white protein and gliadin involvement in the protein network formation during cake making. Thermal denaturation of the different egg white proteins codetermines their incorporation in the network. Ovotransferrin, ovomucoid and lysozyme are the first to be incorporated in the network. In the process, sulfhydryl/disulfide exchange reactions with other proteins play a key role. In a later phase, ovalbumin is also incorporated. The latter has free sulfhydryl groups and further reacts with α- and γ-gliadins by sulfhydryl/disulfide exchange reactions. Our work demonstrates for the first time a mixed network in cake which contains protein from both egg white and wheat flour. The ω-gliadins lack both sulfhydryl groups and disulfide bonds and are not incorporated in the protein network. Graphical abstract: Highlights: Egg white and wheat flour proteins take part in the same covalent network. Ovalbumin determines the incorporation of α- and γ-gliadin. Other egg white proteins form disulfide bonds with proteins from other ingredients. ω-Gliadin is not incorporated in the covalent protein network in pound cake.